2012
DOI: 10.1074/jbc.m112.396176
|View full text |Cite
|
Sign up to set email alerts
|

Tau Oligomers Impair Artificial Membrane Integrity and Cellular Viability

Abstract: Background: Tau aggregation is a multistep process. The identity of Tau species compromising cell viability remains largely unknown. Results: Analysis of Tau aggregation dynamic identifies oligomeric Tau aggregates as toxic species that impair viability. Conclusion: Membrane leakage induced by oligomeric Tau is a mechanism for toxicity. Significance: Tau belongs to the class of amyloidogenic proteins that share a common toxicity-mediating mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
156
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(168 citation statements)
references
References 69 publications
10
156
2
Order By: Relevance
“…This stimulates macropinocytosis, a form of fluid phase endocytosis, to bring pathogenic "seeds" into the cell, and underlies transcellular propagation (10). Recent studies have suggested that uptake of exogenous Tau depends on aggregate size (11) and that smaller Tau assemblies could be disruptive to membranes (12). However, the minimum Tau assembly that can spontaneously bind the cell membrane, trigger cell uptake, and serve as a template for aggregation of Tau is not known.…”
mentioning
confidence: 99%
“…This stimulates macropinocytosis, a form of fluid phase endocytosis, to bring pathogenic "seeds" into the cell, and underlies transcellular propagation (10). Recent studies have suggested that uptake of exogenous Tau depends on aggregate size (11) and that smaller Tau assemblies could be disruptive to membranes (12). However, the minimum Tau assembly that can spontaneously bind the cell membrane, trigger cell uptake, and serve as a template for aggregation of Tau is not known.…”
mentioning
confidence: 99%
“…Although the mechanism of tau toxicity is subject to some debate, increasing evidence suggests that a prefibrillar oligomeric state of tau is the primary toxic species responsible for neurodegeneration (6,7), similar to models proposed for many other amyloid-forming proteins. According to this model, tau dissociates from microtubules and forms oligomers with the potential to disrupt cellular membranes and impair synaptic and mitochondrial function before ultimately forming relatively inert amyloid fibrils in what may or may not be a protective mechanism to remove toxic oligomers (6)(7)(8). How cells control the relative populations of tau monomers, oligomers, and fibrils, and protect against associated toxicity, remains poorly understood.…”
mentioning
confidence: 99%
“…An interesting UV raman spectroscopy study showed that at early stages, within the first hour, fibrillar aggregates possess a mixture of β-sheet and disordered content. Afterward, the UVRR spectra shows a consolidation in fibril structure, augmenting the content of β sheet [15], interesting is to remark that toxicity apparently relies on β sheet content [16]. …”
mentioning
confidence: 99%